Effects of SRY (Sex Determining Region Y)-Box 9 (SOX9) and Telomerase Reverse Transcriptase (TERT) genes transfection in chondrocytes seeded on three-dimensional scaffolds: gross observation and cell proliferation assay - Md Nazir, Noorhidayah; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zainol, Ismail; Zamli, Zaitunnatakhin; Sha'ban, Munirah (6 Frontiers Media S.A, 2016)
Purpose: To evaluate the formation of in vitro 3D tissue constructs engineered from the SOX9 and TERT genes post-transfected chondrocytes seeded on poly(lactic-co-glycolic acid)(PLGA) based scaffolds. Methods: With the approval of Institutional Animal Care and Use Committee (IACUC,IIUM), the post-transfected rabbits’ chondrocytes were seeded on the prefabricated PLGA with and without fibrin scaffolds. The resulting constructs were cultured for three-week. This experiment setting examined the following groups: (1) non-transfected chondrocytes (control), (2) SOX9-transfected chondrocytes, (3) TERT-transfected chondrocytes and (4) SOX9/TERT-transfected chondrocytes; each seeded on PLGA and PLGA/fibrin scaffolds. All eight groups were evaluated for gross morphology and cells proliferation activity. Results: Grossly, all constructs shrunk in size. The PLGA/fibrin constructs showed a glass-like appearance throughout the culture. The chondrocytes seeded in PLGA/fibrin number showed an increment pattern from day-1 to -21 compared to chondrocytes seeded in PLGA only. The SOX9/TERT-transfected chondrocytes seeded on PLGA/fibrin showed a steadily increased growth pattern comparable to that of control group. Both SOX9 and TERT genes may have synergistic effect in maintaining cell proliferation activity in 3D scaffolds. Overall cellular growth pattern seemed better in PLGA/fibrin than PLGA alone. Besides, PLGA/fibrin constructs exhibited a more stable macroscopic structure throughout the in vitro culture making it a suitable candidate for implantation purpose. Further in vitro study involving construct’s weight, histology analysis, genes expression, biochemical assessments and in vivo implantation are currently underway.